2008
DOI: 10.1142/s0217751x08039396
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extra Dimension in Accelerated Expansion

Abstract: A five-dimensional FRW-type Kaluza–Klein cosmological model is taken to study the role of extra dimension in the expansion of the universe. Relation between scale factors corresponding to conventional four dimensions and the extra dimension has been established. Field equations are solved in order to find out the effect of pressure corresponding to these scale factors. Conditions for accelerated expansion are derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Further, it is now well established that the universe is accelerating in the present epoch [14,15]. To consider the phenomenon of acceleration of the universe some researchers have suggested that this acceleration is due to the cosmological constant or dark energy [16][17][18].…”
mentioning
confidence: 99%
“…Further, it is now well established that the universe is accelerating in the present epoch [14,15]. To consider the phenomenon of acceleration of the universe some researchers have suggested that this acceleration is due to the cosmological constant or dark energy [16][17][18].…”
mentioning
confidence: 99%
“…We have already found the solution of field equations by taking the direct proportionality between the pressures corresponding to the usual four dimensions and the extra dimension [54,55]. Our results were extended in reference [39] by taking a fixed cosmological constant.…”
Section: Solution Of the Field Equationsmentioning
confidence: 59%
“…In our earlier work [54,55] we had shown that the extra dimension plays an important role in acceleration of the universe. On the other hand, it is also known that the cosmological constant is always corresponds to a negative pressure.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations